1998
DOI: 10.1210/jcem.83.11.5236
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expression of Estrogen Receptor α and β Isoforms in Human Pituitary Tumors1

Abstract: The physiological effects of estrogen on the pituitary, including cellular proliferation and regulation of hormone synthesis, are mediated by the nuclear estrogen receptor (ER). The ER acts as a dimer to modulate gene transcription and contains specific functional domains encoded in different exons. Two separate, but related, forms of the receptor (ERalpha and ERbeta) exist, with distinct tissue and cell patterns of expression. Additional ER isoforms, generated by alternative messenger ribonucleic acid (mRNA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 35 publications
0
7
0
4
Order By: Relevance
“…ERα has been limited to LTs and GTs, where it could modulate gonadal steroid estrogen (E 2 )-mediated gene expression [23]. In a previous study of 71 human PitNETs, the analysis of ER mRNA by RT-PCR showed significant expression of ERα in all LTs and in 61% of GTs [24]. Simultaneously, another study evaluating the mRNA expression of ERα and ERβ in 38 PitNETs found co-expression of both receptors in 60% of LTs and 29% of GTs.…”
Section: Discussionmentioning
confidence: 99%
“…ERα has been limited to LTs and GTs, where it could modulate gonadal steroid estrogen (E 2 )-mediated gene expression [23]. In a previous study of 71 human PitNETs, the analysis of ER mRNA by RT-PCR showed significant expression of ERα in all LTs and in 61% of GTs [24]. Simultaneously, another study evaluating the mRNA expression of ERα and ERβ in 38 PitNETs found co-expression of both receptors in 60% of LTs and 29% of GTs.…”
Section: Discussionmentioning
confidence: 99%
“…In females, disruption of the ERβ gene results in reduced litter size (40), but this subfertility is suggested to occur through abnormalities in other reproductive tissues; in males, there is little decrease in fertility (41, 42). These models suggest that only ERα plays an important role in the pituitary, even though low levels of ERβ mRNA expression have been described in nearly every adult pituitary cell type (34, 43–46). However, ERβ may play a role in oestrogen actions in specific cell types, or during specific developmental stages.…”
Section: Expression and Regulation Of Oestrogen Receptor Isoformsmentioning
confidence: 99%
“…However, ERβ may play a role in oestrogen actions in specific cell types, or during specific developmental stages. For example, in human pituitary, only ERβ is expressed in corticotropes and somatotropes, and this may explain some direct effects of oestrogen on ACTH and GH that were puzzling in cells that do not express ERα (43, 44). Few studies have measured ERβ protein, and the protein expression may have a more restricted pattern than the mRNA (47).…”
Section: Expression and Regulation Of Oestrogen Receptor Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…ER and other steroid receptors are thought to act primarily as homodimers, although ER␣-ER␤ dimers can be observed on DNA and in solution (5)(6)(7). Because the isoforms are expressed in a tissue-and cell-specific manner (8,9) and have differential affinities for synthetic and environmental ligands (10), dimer formation can have important biological consequences. For example, ER isoforms ␣ and ␤ have markedly different responses to estrogen antagonists, and the ratio of the two isoforms could determine cellular responses to these drugs (10 -12).…”
Section: Estrogen Receptors (Ers)mentioning
confidence: 99%